عالمية اللغة العربية: قراءة إبستيمية في إمكانية الاستثمار اللغوي: اللغة العربية، استخدام اللغة، العالمية، الاستثمار، التقنية - Chettouh, Zhour (Al-Ḍād Journal, 2019)
The reality of the Arabic language today confirms that the Arabic language is a crude economic resource marginalized by its users, at a time when the civilized world is aiming to maximize its economic revenues The use of the mother language and its advancement, based on its dissemination in the technical fields, and this work is a long-term investment is beneficial if the cultural institutions invested well. In fact, the relationship between language and economy is A correlation relationship. If flourished language flourished economy and vice versa, This research comes to highlight the highlight of the Arabic language of the energies of expression, guaranteed to stay and save from change , It is a language that is effective in conveying experiences, feelings. It has been and remains a scientific language that has been able to meet the needs of its users over the course of many centuries, exceeding sixteen centuries.